2015
DOI: 10.3109/13880209.2014.993042
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of theAnnona glabrafruit and their cytotoxic activity

Abstract: Context: Traditional Chinese medicines have attracted increasing interest as potential sources of novel drugs with a wide range of biological and pharmacological activities. Annona glabra Linn (Annonaceae) is used in traditional medicine as an anticancer drug. Phytochemical investigation of this plant led to the isolation of acetogenins, ent-kauranes, peptides, and alkaloids. In addition, compounds exhibited anticancer, anti-HIV-reserve, and antimalaria. Objective: Isolation, structure determination, and cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…increased the level of c-caspase-3, -9, Bax, while decreasing the level of Bcl-2 [64]. Elevated expression level of c-caspase-3, Bax and suppressed expression of Bcl-2, c-myc, p-AKT were demonstrated following the treatment of icariside D 2 [65]. Also, icariside II treatment promoted c-caspase-3 activity, c-PARP, PTP and SHP-1 expression in U937 cells.…”
Section: Natural Compounds and Acute Myeloid Leukemiamentioning
confidence: 99%
“…increased the level of c-caspase-3, -9, Bax, while decreasing the level of Bcl-2 [64]. Elevated expression level of c-caspase-3, Bax and suppressed expression of Bcl-2, c-myc, p-AKT were demonstrated following the treatment of icariside D 2 [65]. Also, icariside II treatment promoted c-caspase-3 activity, c-PARP, PTP and SHP-1 expression in U937 cells.…”
Section: Natural Compounds and Acute Myeloid Leukemiamentioning
confidence: 99%
“…Thus, the absolute configuration of 1 was determined as 2 E ,4 E ,1’ R ,3’ S ,5’ R ,8’ S, and the structure of 1 was elucidated as (2 E ,4 E )-dihydrophaseic acid methyl ester-3- O - β -D-glucopyranoside. To the best of our knowledge, recently, free acid and glucoside ester of compound 1 were reported from Annona glabra fruit [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, more attentions have been paid on the pharmacological studies of icariside D2. It has been reported that icariside D2 had synergistic inhibitive effect on angiotensin-converting enzyme [4] and remarkable anticancer activity to kill leukemia cells in vitro [5], demonstrating the therapeutic and nutraceutical potential of icariside D2 in the health care industry.…”
Section: Introductionmentioning
confidence: 99%
“…Although icariside D2 has been identified from several plants such as Epimedium [1], Apium graveolens [4], Annona glabra [5], Ficus microcarpa [6], Tinospora sinensis [7], and Rhodiola crenulata [8], extraction of icariside D2 suffers low yields for the low content and limited plant resources. Chemical synthesis for glycoside products has always been frustrated by the diversity of stereochemistries and regiochemistries, and generally requires multiple protection and deprotection steps to achieve regio-selectivity in glycosylation [9].…”
Section: Introductionmentioning
confidence: 99%